Assessment of Abdominal Fat Compartments Using DXA in Premenopausal Women From Anorexia Nervosa to Morbid Obesity. (13th June 2013) - Bredella, Miriam A.; Gill, Corey M.; Keating, Leigh K.; Torriani, Martin; Anderson, Ellen J.; Punyanitya, Mark; Wilson, Kevin E.; Kelly, Thomas L.; Miller, Karen K.
<x xml:space="preserve">Abstract</x> Objective: To test a newly developed dual energy X‐ray absorptiometry (DXA) method for abdominal fat depot quantification in subjects with anorexia nervosa (AN), normal weight, and obesity using CT as a gold standard. Design and Methods: 135 premenopausal women (overweight/obese: n = 89, normal‐weight: n = 27, AN: n = 19); abdominal visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), and total adipose tissue (TAT) areas determined on CT and DXA. Results: There were strong correlations between DXA and CT measurements of abdominal fat compartments in all groups with the strongest correlation coefficients in the normal‐weight and overweight/obese groups. Correlations of DXA and CT VAT measurements were strongest in the obese group and weakest in the AN group. DXA abdominal fat depots were higher in all groups compared to CT, with the largest % mean difference in the AN group and smallest in the obese group. Conclusion: A new DXA technique is able to assess abdominal fat compartments including VAT in premenopausal women across a large weight spectrum. However, DXA measurements of abdominal fat were higher than CT, and this percent bias was most pronounced in the AN subjects and decreased with increasing weight, suggesting that this technique may be more useful in obese individuals.